Northern Science and Research: Postsecondary Perspectives in the Northwest Territories - Paci, Chris; Hodgkins, Andrew; Katz, Sharon; Braden, Jazzan; Bravo, Michael; Gal, Ruth Ann; Jardine, Cindy; Nuttall, Mark; Erasmus, Joanne; Daniel, Steven (Journal of Northern Studies, 2008)
The International Polar Year (IPY) provides an opportunity to reflect on Northern science and research. For all Canadians, science and research should contribute to living a good life. A good life includes successfully making sense of the world within local contexts, sharing this knowledge beyond the immediate community and reconciling it with knowledge held by outsiders. Northern science and research are inherent in Traditional Dene, Inuvialuit and Métis knowledge; and they continue to be reflected in Northern governance, economy, and cultures. Alongside Aboriginal sciences are Western sciences; these are primarily disciplinary in nature and formally structure postsecondary education globally. Postsecondary science and research education is still being introduced to the Northwest Territories (NWT). Over the last forty years the territorial government has developed the capacity for educational services, funding, institutions, and authority through the Department of Education, Culture and Employment. The delivery of Northern-based postsecondary education through Aurora College provides Northerners with the capacity to generate science and research in the North. What place do science and research have in the North? (North in this paper demarcates the socially constructed geopolitical territories north of the 60th parallel that we use cautiously as a structural term for the purposes of our narrative.) What kinds of investments need to be made and will Northerners be prepared to overcome barriers and take advantage of the opportunities?